Enhancement of the Magnetic Coupling in Exfoliated CrCl3 Crystals Observed by Low‐Temperature Magnetic Force Microscopy and X‐ray Magnetic Circular Dichroism. Issue 24 (10th May 2020) - Serri, Michele; Cucinotta, Giuseppe; Poggini, Lorenzo; Serrano, Giulia; Sainctavit, Philippe; Strychalska‐Nowak, Judyta; Politano, Antonio; Bonaccorso, Francesco; Caneschi, Andrea; Cava, Robert J.; Sessoli, Roberta; Ottaviano, Luca; et al.
Abstract: Magnetic crystals formed by 2D layers interacting by weak van der Waals forces are currently a hot research topic. When these crystals are thinned to nanometric size, they can manifest strikingly different magnetic behavior compared to the bulk form. This can be the result of, for example, quantum electronic confinement effects, the presence of defects, or pinning of the crystallographic structure in metastable phases induced by the exfoliation process. In this work, an investigation of the magnetism of micromechanically cleaved CrCl3 flakes with thickness >10 nm is performed. These flakes are characterized by superconducting quantum interference device magnetometry, surface‐sensitive X‐ray magnetic circular dichroism, and spatially resolved magnetic force microscopy. The results highlight an enhancement of the CrCl3 antiferromagnetic interlayer interaction that appears to be independent of the flake size when the thickness is tens of nanometers. The estimated exchange field is 9 kOe, representing an increase of ≈900% compared to the one of the bulk crystals. This effect can be attributed to the pinning of the high‐temperature monoclinic structure, as recently suggested by polarized Raman spectroscopy investigations in thin (8–35 nm) CrCl3 flakes. Abstract : Low‐temperature magnetic force microscopy (MFM) and X‐ray magnetic circular dichroism are used to investigate micromechanically cleaved flakes of chromium trichloride crystals, revealing a ninefold increase of antiferromagnetic coupling between layers after exfoliation. Joint topographic and magnetic measurements by MFM on individual flakes show a common behavior in the 10–50 nm thickness range.